Kwasuka Sukela: re-imagined bodies of a (South African) 1990s born woman - Msezane,Sethembile (Michaelis School of Fine Art, 2022)
Through an analysis of my artistic work, I examine past and present representations of black women in South African public and private domains. Having been confronted with monuments erected to celebrate British colonialism and Afrikaner nationalism, I focus on the paucity of iconic black women in history and mythology. I perform figures who I construct from existing histories and look to the women in my own family archive to memorialise them. For this reason, performance has been key, in my practice, in re-locating the presence of the black female body. In South African architecture, monuments and public sculpture there is a lack of representation of black women. I refer to sites where statues and monuments have been erected to commemorate certain histories. Having experienced these spaces as particularly masculine and racialised, I perform women whom I consider to be significant. As a young black woman investigating current socio-political issues in South Africa, I draw parallels with the past. I embody these women in sculptural installations and in public spaces as living sculptures standing on a white plinth. In relation to these public performances, the exhibition includes sculptural installations that speak to the interplay of public and private domains. Animism and Ubuntu form part of the spiritual agency that is present in this work. Collectively these works narrate resistance and self-assertion in response to dominant ideologies in the public space.